2021
DOI: 10.5194/wcd-2-331-2021
|View full text |Cite
|
Sign up to set email alerts
|

The role of air–sea fluxes for the water vapour isotope signals in the cold and warm sectors of extratropical cyclones over the Southern Ocean

Abstract: Abstract. Meridional atmospheric transport is an important process in the climate system and has implications for the availability of heat and moisture at high latitudes. Near-surface cold and warm temperature advection over the ocean in the context of extratropical cyclones additionally leads to important air–sea exchange. In this paper, we investigate the impact of these air–sea fluxes on the stable water isotope (SWI) composition of water vapour in the Southern Ocean's atmospheric boundary layer. SWIs serve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 93 publications
4
46
0
Order By: Relevance
“…Signals of d-excess in precipitation in these three regions (Fig. 2f,i) are generally consistent with the same processes as above: (1) decreasing d-excess along air parcels moving land inward due to the weak but non-negligible impact of the condensation temperature on the d-excess (Thurnherr et al, 2021, their Appendix A), (2) d-excess tends to be lower when the share of transpiration (non-fractionating) in evapotranspiration is relatively large (Risi et al, 2010a;Aemisegger et al, 2014), which can reasonably be assumed over central Africa, and (3) very low d-excess along the northern fringe of the tropical rain belt due to strong non-equilibrium fractionation during below cloud evaporation in dry air (Araguas-Araguas et al, 2000;Risi et al, 2008a;Graf et al, 2019).…”
Section: Comparison Of Cosmoiso To Gnip Observationssupporting
confidence: 82%
See 1 more Smart Citation
“…Signals of d-excess in precipitation in these three regions (Fig. 2f,i) are generally consistent with the same processes as above: (1) decreasing d-excess along air parcels moving land inward due to the weak but non-negligible impact of the condensation temperature on the d-excess (Thurnherr et al, 2021, their Appendix A), (2) d-excess tends to be lower when the share of transpiration (non-fractionating) in evapotranspiration is relatively large (Risi et al, 2010a;Aemisegger et al, 2014), which can reasonably be assumed over central Africa, and (3) very low d-excess along the northern fringe of the tropical rain belt due to strong non-equilibrium fractionation during below cloud evaporation in dry air (Araguas-Araguas et al, 2000;Risi et al, 2008a;Graf et al, 2019).…”
Section: Comparison Of Cosmoiso To Gnip Observationssupporting
confidence: 82%
“…These heavy isotopes undergo identical processes as the common water isotope H2 16 O except during phase transitions when isotopic fractionation occurs. COSMOiso has been used to study a variety of atmospheric processes in the hydrological cycle in idealized studies (Dütsch et al, 2016), detailed case studies (Pfahl et al, 2012;Aemisegger et al, 2015;Lee et al, 2019), and (semi-)climatological analyses (Dütsch et al, 2018;Christner et al, 2018;Dahinden et al, 2021;Diekmann et al, 2021;Thurnherr et al, 2021).…”
Section: The Cosmoiso Modelmentioning
confidence: 99%
“…In addition, as compared to the cold front, condensation in the west coast of the mainland of Japan showed relatively low d 2 H and high d-excess values (Figs.10b,e). This was caused by moisture along the DI that evaporated from the Sea of Japan with low d 2 H and high d-excess values under a cold and dry continental air mass during cold-air outbreaks (Figs.11b,e), which was consistent with previous studies(Aemisegger and Sjolte 2018;Thurnherr et al 2021).…”
supporting
confidence: 91%
“…It is worth noting the moisture uptake time and the time lag between evaporation from the ocean surface and condensation in the atmosphere. The average uptake time for whole moisture of air parcels was suggested by Thurnherr et al (2021) to be 36 (49) h in the cold (warm) sector for Southern Ocean cyclones. However, in the northwest Pacific region, Hirata et al (2015Hirata et al ( , 2016 showed that about 50% of the moisture (5 g kg 21 ) in air parcels along the CCB was taken up from the underlying ocean within 12 h before condensation, which indicates that the average time lag for moisture transported by the CCB from the underlying ocean to condensation was around 6 h.…”
Section: B Large-scale Environment During Cyclone Developmentmentioning
confidence: 99%
See 1 more Smart Citation